Interference of quercetin in biofilm production by Staphylococcus spp. isolated from cases of goat mastitis - Renata de Moraes Peixoto Araújo; Maura Marinete de Sousa; Letícia Stheffany de Barros Cunha; Rodolfo de Moraes Peixoto; Márcio Rennan Santos Tavares; Mateus Matiuzzi da Costa; Felício Garino Júnior; Eldinê Gomes de Miranda Neto (Ciência Rural)
ABSTRACT: This study explored antimicrobial alternatives and determined the antibacterial and antibiofilm properties of quercetin against Staphylococcus spp. of goat mastitis. Four bacterial isolates from goats with subclinical mastitis were identified by MALDI-TOF MS: S. aureus, S. chromogenes, S. lugdunensis, S. epidermidis and S. aureus ATCC 25923. We determined the in vitro antibacterial activity of quercetin, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). These concentrations ranged from 1 mg/mL to 0.008 mg/mL. Subsequently, the anti-biofilm activity of quercetin was assessed. The results of this study indicated that quercetin showed bacteriostatic and antibiofilm activity. Subinhibitory concentrations (0.5, 0.25, and 0.125 mg/mL) reduced biofilm. The findings of this study provided a direction for the development of new antimicrobial strategies against Staphylococcus spp. causes of caprine mastitis.